(3GdTaG HJYQja Mbhb GdeUWaj (B( (3Udi Gddg Ydjg hSde (B)s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3Ydi GdRYaQGfi Hf jMji GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HESeg GdCSei s
(3BNQgG (B:s
(3hdGjfJUQ ef NPdg , hdGjQO OYhi GdbGUOjf , hdG jUdM Yed GdeaSOjf , hgh MSHfG hfYe Gdhcjd , hUdhGJg Ydi fHjg eMeO NGJe GdfHjjf hYdi Bdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI NRGFfjI s
(3HQSe GdYRjR jhSa Hf HQSHGi HKZQ GdCScfOQjI s
(3HBNQgG ebGHdI SfI (B851 (3g` s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs